Global translational impacts of the loss of the tRNA modification t6A in yeast - Patrick C. Thiaville; Rachel Legendre; Diego Rojas-Benítez; Agnès Baudin-Baillieu; Isabelle Hatin; Guilhem Chalancon; Alvaro Glavic; Olivier Namy; Valérie de Crécy-Lagard (Microbial Cell)
The universal tRNA modification t6A is found at position 37 of nearly all tRNAs decoding ANN codons. The absence of t6A37 leads to severe growth defects in baker’s yeast, phenotypes similar to those caused by defects in mcm5s2U34 synthesis. Mutants in mcm5s2U34 can be suppressed by overexpression of tRNALysUUU, but we show t6A phenotypes could not be suppressed by expressing any individual ANN decoding tRNA, and t6A and mcm5s2U are not determinants for each other’s formation. Our results suggest that t6A deficiency, like mcm5s2U deficiency, leads to protein folding defects, and show that the absence of t6A led to stress sensitivities (heat, ethanol, salt) and sensitivity to TOR pathway inhibitors. Additionally, L-homoserine suppressed the slow growth phenotype seen in t6A-deficient strains, and proteins aggregates and Advanced Glycation End-products (AGEs) were increased in the mutants. The global consequences on translation caused by t6A absence were examined by ribosome profiling. Interestingly, the absence of t6A did not lead to global translation defects, but did increase translation initiation at upstream non-AUG codons and increased frame-shifting in specific genes. Analysis of codon occupancy rates suggests that one of the major roles of t6A is to homogenize the process of elongation by slowing the elongation rate at codons decoded by high abundance tRNAs and I34:C3 pairs while increasing the elongation rate of rare tRNAs and G34:U3 pairs. This work reveals that the consequences of t6A absence are complex and multilayered and has set the stage to elucidate the molecular basis of the observed phenotypes.